Optimisation of EDC parameters using TOPSIS approach. (9th October 2019) - Senthilkumar, C.
Aluminium alloys are extensively used in the aeronautics and automotive industries due to light weight and good specific strength, but it has poor surface property, especially of sliding components. For this reason, a novel surface modification technique has been developed to improve the wear resistance of the material. Therefore, the present work is initiated to investigate the influence of some predominant EDC parameters such as current, pulse-on time and pulse-off time on the deposition layer thickness (DLT) and surface roughness (SR). The experimental plan adopts the face-centred central composite design (CCD) using response surface methodology (RSM). The contour plots were generated to study the effect of process parameters as well as their interactions. Microstructure analysis has been carried out to through scanning electron microscope (SEM). The process parameters are optimised based on TOPSIS. Surface roughness and DLT is uniform with increase in pulse off time. Lower pulse off time, increases the layer thickness and surface roughness.